Process development of the device using in-house plate-to-plate tool with nanoimprint lithography technique for biochip application - Beh, Khi Khim (2016)
Biochip is a promising device with capabilities of performing sorting, trapping and screening a large number of biological samples in a short time. Fabrication of biochip pattern process leads to an opening study towards the development of a working biochip. The traditional photolithography process have a limitation in achieving high throughput for biochip pattern fabrication. In this research, the fabrication process of biochip pattern was developed and the imprint parameter for biochip pattern using an in-house assembled plate-to-plate tool was investigated. The biochip patterns are prepared from existing projection lithography to create the mold. Using soft lithography technique, the biochip pattern was replicated invertly in the PDMS mold. The PDMS mold and in-house plate-to-plate fulfilled the requirement for UV-NIL to imprint biochip patterns on a flexible substrate. Dimension error difference (DED) is the difference between the original design dimensions to fabricated design dimensions. DED was characterized and investigated for precise pattern transfer. UV exposure of 140 W was able to produce the satisfied imprint pattern in biochip pattern mold fabrication. However, higher UV energy caused overexposure in the resist, resulting wider width and bridging. Besides that, crack regions were found when post bake exposure parameters are not properly optimized. The DED between biochip pattern mold and PDMS mold are less compared to biochip pattern mold fabrication in the photolithography process. Critical dimension in the biochip pattern was maintained in the imprint process. However, the higher imprint force will cause an overflow of the resist on the substrate, resulting unsatisfied pattern structure. The proposed parameters for imprinting biochip patterns using in-house plate-to-plate tool are 80 N range and 20 seconds of UV exposure.